Inequities in access to health care in different health systems: A study in municipalities of central Colombia and north-eastern Brazil (2014)
Introduction. Health system reforms are undertaken with the aim of improving equity of access to health care. Their impact is generally analyzed based on health care utilization, without distinguishing between levels of care. This study aims to analyze inequities in access to the continuum of care in municipalities of Brazil and Colombia. Methods. A cross-sectional study was conducted based on a survey of a multistage probability sample of people who had had at least one health problem in the prior three months (2,163 in Colombia and 2,167 in Brazil). The outcome variables were dichotomous variables on the utilization of curative and preventive services. The main independent variables were income, being the holder of a private health plan and, in Colombia, type of insurance scheme of the General System of Social Security in Health (SGSSS). For each country, the prevalence of the outcome variables was calculated overall and stratified by levels of per capita income, SGSSS insurance schemes and private health plan. Prevalence ratios were computed by means of Poisson regression models with robust variance, controlling for health care need. Results: There are inequities in favor of individuals of a higher socioeconomic status: in Colombia, in the three different care levels (primary, outpatient secondary and emergency care) and preventive activities; and in Brazil, in the use of outpatient secondary care services and preventive activities, whilst lower-income individuals make greater use of the primary care services. In both countries, inequity in the use of outpatient secondary care is more pronounced than in the other care levels. Income in both countries, insurance scheme enrollment in Colombia and holding a private health plan in Brazil all contribute to the presence of inequities in utilization. Conclusions: Twenty years after the introduction of reforms implemented to improve equity in access to health care, inequities, defined in terms of unequal use for equal need, are still present in both countries. The design of the health systems appears to determine access to the health services: two insurance schemes in Colombia with different benefits packages and a segmented system in Brazil, with a significant private component. © 2014 Garcia-Subirats et al.; licensee BioMed Central Ltd.